Comparison of clot‐based, chromogenic and fluorescence assays for measurement of factor VIII inhibitors in the US Hemophilia Inhibitor Research Study. Issue 7 (15th July 2013) - Miller, C. H.; Rice, A. S.; Boylan, B.; Shapiro, A. D.; Lentz, S. R.; Wicklund, B. M.; Kelly, F. M.; Soucie, J. M.
Summary: Background: Detection and validation of inhibitors (antibodies) to hemophilia treatment products are important for clinical care, evaluation of product safety and assessment of population trends. Methods: Centralized monitoring for factor VIII (FVIII) inhibitors was conducted for patients in the Hemophilia Inhibitor Research Study using a previously reported modified Nijmegen‐Bethesda clotting assay (NBA), a chromogenic Bethesda assay (CBA) and a novel fluorescence immunoassay (FLI). Results: NBA and CBA were performed on 1005 specimens and FLI on 272 specimens. CBA was negative on 880/883 specimens (99.7%) with Nijmegen‐Bethesda units (NBU) < 0.5 and positive on 42/42 specimens (100%) with NBU ≥ 2.0 and 43/80 specimens (53.8%) with NBU 0.5–1.9. Among specimens with positive NBA and negative CBA, 58.1% were FLI negative, 12.9% had evidence of lupus anticoagulant, and 35.5% had non‐time‐dependent inhibition. CBA and FLI were positive on 72.4% and 100% of 1.0–1.9 NBU specimens and 43.1% and 50.0% of 0.5–0.9 NBU specimens. FLI detected antibodies in 98.0% of CBA‐positive and 81.6% of NBA‐positive specimens ( P  =   0.004). Among 21 new inhibitors detected by NBA, five (23.8%) with 0.7–1.3 NBU did not react in CBA or FLI. Among previously positive patients with 0.5–1.9 NBU, 7/25 (28%) were not CBA or FLI positive. FLI was positive on 36/169 NBU‐negative specimens (21.3%). Conclusions: FVIII specificity could not be demonstrated by CBA or FLI for 26% of inhibitors of 0.5–1.9 NBU; such results must be interpreted with caution. Low titer inhibitors detected in clot‐based assays should always be repeated, with consideration given to evaluating their reactivity with FVIII using more specific assays.